Seasonal and Spatial Variations of Iron and Zinc Values in Meadows with a Semi-Arid Climate: Seasonal Changes in the Climate by Iron and Zinc - Bashir, Humayun; Khan, Zafar Iqbal; Ahmad, Kafeel (Biological Sciences - PJSIR, 2021)
Seasonal changes in the climate, as well as in plants and species living in this environment, which causes serious problems. Current work was carried out to evaluate the seasonal impact on the concentration of iron (Fe) and zinc (Zn) in soil, forages and animals. A semi arid dry climatic area of Pakistan was selected to find out the seasonal effects on soil and availability of Zn and Fe, and its translocation to forages and animals. Twenty seven forages were collected and 320 ruminant samples collected from two sites in four seasons. Effect of spatial-temporal variations were studied on the ruminants of four physiological stages (Does, Bucks, Wether and Juvenile). Different sources from goats including blood, feces and urine were collected for the analysis of Zn and Fe. Results showed that both elements in soil were significantly (P < 0.05) affected by season and site x season. In forages, only site showed significant effect on Fe and Zn, while Zn was affected non-significantly (P > 0.05) by season and site x season. Zn and Fe in goats were non-significantly affected by season and source x stages, while significantly affected by sites and sources. All values of both elements were in safe limits except deficiency of Fe (1.69 to 2.33 mg/L) in blood. Results of health indices were also in the limits. Current work encircles the spatio- temporal effects on mineral availability in the food chain and also concern the health effects related to ruminant health.